THE CONCEPT OF INTERFERENCE AND ITS CHARACTERISTICS IN KOREAN LINGUISTICS - Rasulova Nodira Baxtiyorovna (Web of Journals Publishing, 2024)
Interference as a linguistic phenomenon is studied from various perspectives, including from the perspective of the features of speech in a second language that are characteristic of certain social, professional, and age groups. This article examines the concept of the phenomenon of interference in linguistics. The characteristics of interference and approaches to its direction are determined.
Keywords: Linguistics, interference, language, bilingualism, intercultural communication.